2019
DOI: 10.3390/cancers11111776
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of 15-LOX-1 Induces Radioresistance through Downregulation of MacroH2A2 in Colorectal Cancer

Abstract: Despite the importance of radiation therapy, there are few radiation-related markers available for use in clinical practice. A larger catalog of such biomarkers is required to help clinicians decide when radiotherapy should be replaced with a patient-specific treatment. Arachidonate 15-lipoxygenase (15-LOX-1) enzyme is involved in polyunsaturated fatty acid metabolism. When colorectal cancer (CRC) cells were exposed to radiation, 15-LOX-1 was upregulated. To verify whether 15-LOX-1 protects against or induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Overexpression of cPLA2, LOXs and COXs also contributes to the radioresistance of tumors [154][155][156]. It has been reported that overexpression of 15-LOX-1 in colorectal cancer cells exposed to radiation induces radiation resistance through downregulation of MacroH2A2 [157]. Additionally, 12-LOX inhibitors (baicalein or bmd122) have been demonstrated to sensitize prostate cancer cells to radiation [158].…”
Section: Arachidonic Acid Metabolismmentioning
confidence: 99%
“…Overexpression of cPLA2, LOXs and COXs also contributes to the radioresistance of tumors [154][155][156]. It has been reported that overexpression of 15-LOX-1 in colorectal cancer cells exposed to radiation induces radiation resistance through downregulation of MacroH2A2 [157]. Additionally, 12-LOX inhibitors (baicalein or bmd122) have been demonstrated to sensitize prostate cancer cells to radiation [158].…”
Section: Arachidonic Acid Metabolismmentioning
confidence: 99%
“…Upregulation of 5-LOX and 12-LOX activities in cancer contrast with the decrease in 15-lipoxygenase (15-LOX) isoform 1 (15-LOX-1) function, as well as in the metabolites generated from linoleic acid oxidation, such as 13-hydroperoxyoctadecadienoic acid (13(S)-HpODE) [178] and 13-S-hydroxyoctadecadienoic acid (13-S-HODE), which are reported in human colorectal and esophageal cancers [173]. These effects might be related to a downregulation of the 15-LOX-1 gene expression or its inactivation, as demonstrated for colon cancer [182][183][184][185], where the transcription factor GATA-6 is responsible for this effect [183]. Other derived hydroperoxides from 15-LOX-1, such as hydroperoxyoctadecatrienoic acid (13-HpOTrE), 13-HpODE, and 15-hydroperoxyeicosatetraenoic acid (15-HpETE) have been reported as inhibitors of breast, colon, prostate, lung, and leukemia cancer growth in conventional cell studies in vitro [186], supporting that stimulation of this 15-LOX-1 could be potentially used for therapeutical purposes.…”
Section: Alox15bmentioning
confidence: 99%
“…They examined its effects on primary human organoid cultures representing normal colon, colon adenocarcinoma, and rectal adenocarcinoma, and found that it could inhibit the growth of each line. Lysyl oxidase (Lox) is a copper-dependent enzyme encoded by Lox gene [14,15]. Clinical studies have investigated the association between Lox expression and clinicopathological features, progression, and prognosis of GI cancers, including colorectal, esophageal, Hepatocellular Carcinoma (HCC), gastric, and pancreatic carcinoma.…”
Section: Enzymatic Contentmentioning
confidence: 99%